Iron‐Catalyzed Synthesis of Secondary Amines: On the Way to Green Reductive Aminations. Issue 11 (4th September 2014) - Stemmler, Tobias; Surkus, Annette‐Enrika; Pohl, Marga‐Martina; Junge, Kathrin; Beller, Matthias
Abstract Amines represent important intermediates in chemical and biological processes. Herein, we describe the use of a nanostructured iron‐based catalyst for the tandem reductive amination between nitroarenes and aldehydes using hydrogen as reductant. The nanostructured iron‐catalyst is prepared by immobilization of an iron–phenanthroline complex onto a commercially available carbon support. In the reaction sequence a primary amine is formed in situ from the corresponding nitro compound. Reversible condensation with aldehydes forms the respective imines, which are finally reduced to the desired secondary amine. This synthesis of secondary amines is atom‐economical and environmentally attractive using cheap and readily available organic compounds as starting materials.